The Process Evaluating Training & Development of Post Covid-19 Employees at PT. Indocement Tunggal Prakarsa Tbk. (Plant-12) Kalsel - Adani Fildza Muzdalifah; Arif Hartono (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study aims to determine the process of evaluating training & development of post-covid-19 employees at PT Indocement Tunggal Prakarsa Tbk (P-12). This company is located in Tarjun Village, Kotabaru Regency, South Kalimantan. This research uses a descriptive qualitative approach method. Data collection techniques were carried out by conducting observations during the implementation of the internship, conducting interviews with three resource persons from PT Indocement Tunggal Prakarsa Tbk. (P-12). The form of training during the covid-19 pandemic switched to digital platforms such as google meet, zoom and microsoft teams, for the types of training programs that have proven successful, namely those related to SAE, Soft Competency, Engineering and Technical. The obstacles during the covid-19 pandemic are signal networks, minimal interaction, no practice and less than optimal training.